CALCIUM STATUS IN SUDANESE CANCER PATIENTS ATTENDING THE INSTITUTE OF NUCLEAR MEDICINE, MOLECULAR BIOLOGY AND ONCOLOGY - Hamad, Fatima A.; Elhaj, Ahmed M.; Eltom. Ali, Khalid; A.Yousif, Mirghani (مجلة الجزيرة للعلوم الصحية; مجلد 1 عدد 2 (2005), 2005)
Objective: The aim of this study was to study the incidence of hypercalcaemia together with the related biochemical parameters and anthropometric measurements in Sudanese cancer patients attending the Institute of Nuclear Medicine, Molecular Biology and Oncology (INMO), Gezira State, Sudan. Methods, materials and study subjects: The study was a prospective study performed on 100 cancer patients (age ranging between 4- 70 years). The study period was from 15/4/2003 to1/9/2003.  Another 100 persons (age and sex matched) were used as control group. The biochemical parameters measured in this study were serum calcium, serum inorganic phosphorus and serum albumin. Calcium, inorganic phosphorus and albumin were measured by Spectrophotometery. Anthropometrics measurements determined were weight and height. A questionnaire was filled in order to obtain information regarding: age, sex, residence, tribe and information about education, occupation, marital status and past medical history. Type of cancer, date of diagnosis, stage of cancer, treatment, and present complaints were recorded. Results: Hypercalcaemia was detected in ten of the patients (10%). This is similar to the internationally published rates. The types of cancers associated with hypercalcaemia were cancer of the breast (20%), skin (20%), prostate (10%), bladder (10%), rectum (10%), unknown primary (10%) and hematological malignancies (20%).Mean serum calcium (9.48 ± 1.07 mg/dL) and inorganic phosphorus (4.45 ± 1.01 mg/dL) were higher in the cancer patients than the control group (9.03 ± 0.56, 4.13 ± 0.72 mg/dL respectively). However, the difference is statistically not significant. Serum albumin concentration was similar in the patients and control groups (4.97±0.63 and 4.93±0.41 g/dL respectively). The differences of weight and height were not significantly different in the two groups.                                                                                                                                      Conclusion: It is concluded that the calcium, phosphorus and albumin levels among Sudanese individuals were similar to the internationally published levels. Hypercalcaemia is not a rare condition among cancer patients and should be checked whenever there is a symptom because it can lead to many serious complications.